Transitioning farm bill programs to a payment for ecosystem services approach - Heimlich, Ralph E., author; Toombs, Ted, author (Colorado State University. Libraries, 2009)
Farm bill programs currently provide a "pseudo-market" for conservation where a contract between the public and the government (the farm bill) is intermediated by the USDA. In this pseudo market, the USDA provides payments for management practices, which can lead to ecosystem service benefits. But, it does not currently pay directly for the ecosystem service benefits themselves. The goal of this presentation is to highlight considerations for USDA and private landowners (ranchers in particular) if USDA were to transition to a PES approach. I contrast the current system with a PES, and illustrate that significant differences might emerge in the size and character of the "markets" under each scenario. Many difficult questions would need to be addressed to determine how the profitability of a ranch would potentially be affected by a switch to a PES approach.
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. Ted Toombs is affiliated with Environmental Defense Fund, Center for Conservation Incentives. Ralph Heimlich is affiliated with Agricultural Conservation Economics (ACE).
Keywords: USDA; PES; rangeland ecosystem services; payment for ecosystem services; farm bill programs; United States Department of Agriculture